Accounting Comic Effect: Perancangan Komik Edukasi Untuk Meningkatkan Pemahaman Mahasiswa/i Non Akuntansi Terhadap Kasus Misappropriation Of Assets - Ho Erik Hosan; Bonnie Soeherman; Lucya Erlinda Sonia (Akuntansi dan Teknologi Informasi, 2017)
This research is motivated by the difficulty problem to understand about accounting, because a lot of people think that this subject only teach how to make journal entries and present the financial statement. Where, in real conditions, accounting subject is not only learn about it. In addition, the lack of interest in reading will affect the students to understand what the material that being taught. Thus the researcher provide interesting and innovative learning media to avoid the boredom, with education comic by using topic about fraud as a part of accounting. The fraud case is about the misappropriation of asset that are tested on non accounting’s students. This research is conducted with 3 (three) steps using interview, observation, and analysis of document, that is to asked questions about the prior knowledge about fraud. After that, the researcher give the article. An then the last step is to read the comic that have been designed with a similar case from the previous reading. The researcher asked the difference felt after reading the comic and article. The result of research based on display, content, use of language, and interest in reading, all the research’s objects prefer reading comic than article. In addition is easier to understand because comic can described in detail and using language that can be adapted the character of research’s objects and hope the comic book can be applied at the university to make more fun learning.